IMPLEMENTASI PENDIDIKAN KARAKTER TERHADAP PERILAKU SISWA DI KELAS IV SD NEGERI 173422 POLLUNG TAHUN PELAJARAN 2023/2024 - Tarigan, Juniko Esra; Meilana, Indah; Situmorang, Putri Febriani (Universitas Quality, 2024)
This research was conducted in class IV-A of SD Negeri 173422 Pollung consisting of 19 participants. The research method is quantitative descriptive. This method aims to create a systematic, factual and accurate picture of the facts of the relationship between the phenomena studied. The form of implementation of character education in class IV-A of SD Negeri 173422 Pollung is realized through integration in self-development programs, integration in learning activities and character values developed by the school. Thus it can be concluded that the character values developed in class IV-A of SD Negeri 173422 Pollung are religious, honest, disciplined, friendly/communicative, responsible, and tolerant values.